FINANCIAL RESULTS FOR ACCOUNTING AND TAX ACCOUNTING PURPOSES - O. Diakonova; M. Davydkina (Вестник университета)
In the article the problems of convergence of accounting and tax accounting of financial results are considered. The way of recognizing income in formulating financial results is analyzed. Besides, main aspects of accounting and tax accounting of financial results were studied.